The Impact of Miswak (Salvadora Persica) on Periodontal Health: A Review - Qurdahji, Banan T.; Alassaf, Rawan M.; Abu Qbitah, Reem Sameer (South Eastern European Journal of Public Health, 2024)
The importance of periodontal health is being emphasized worldwide, highlighting the need for effective oral hygiene practices. Miswak (Salvadora persica) is a traditional tool with potential oral health benefits. This study aims to review and assess the evidence regarding the effectiveness of Miswak for maintaining periodontal health. A comprehensive literature search was conducted across multiple databases, including Wiley, SCOPUS, CINAHL, MEDLINE, and the Cochrane Library, focusing on studies published from 2019 to 2024. The search was methodically carried out to ensure thorough coverage. Inclusion criteria consisted of English-language, peer-reviewed studies that assessed the impact of Salvadora persica (Miswak) on oral health, specifically concerning periodontal disease or periodontitis, as directly addressed in original research publications, systematic reviews, or clinical trials published in English. Exclusion criteria involved editorials, opinion pieces, references unrelated to Salvadora persica's effects on oral health, and references not available in full text. A total of 97 studies were screened, yielding five eligible studies: one systematic review and meta-analysis, three randomized controlled trials (RCTs), and one randomized crossover trial. Across the reviewed studies, Miswak demonstrated notable effectiveness in controlling plaque and gingivitis compared to standard oral hygiene methods. The studies collectively demonstrate the effectiveness of Salvadora persica (Miswak) as an oral hygiene tool, particularly in reducing plaque and gingivitis. In several instances, Miswak performed better than traditional toothbrushes, as seen in plaque reduction and improvements in gingival health metrics.